The Influence of Small and Medium Enterprise Actors’ Knowledge About Sharia’ Banking Towards Their Interest to Use Musyarakah Financing Product - Siti Nur Azizah; Anissa Arum Lestari (EKSYAR : Jurnal Ekonomi Syari'ah & Bisnis Islam (e-Journal), 2022)
Micro Small and Medium Enterprises (SME) has an important and strategic role in national scale of economic growth. The development of SME itself often times faces various dilemmas such as budgeting problem that lacks of capital either by numbers or sources. Meanwhile, SME is a great potential market for financial service industry especially bank to distribute financing. Sharia banking has budgeting core product in the form of profit sharing developed in the funding product called musyarakah. One of fundamental factor to attract the interest of SME agent to use the musyarakah funding is to impart the knowledge concerning sharia banking. This research is conducted to observe the effect of SME agents’ sharia Banking Knowledge toward their interest of choosing musyarakah as financing product. The independent variable of this research is knowledge that consists of Islamic work ethic in sharia banking knowledge, operational principle in sharia banking knowledge, knowledge of products in sharia banking, knowledge of profit sharing in sharia banking, risk of funding in sharia banking knowledge while the dependent variable is the interest to use musyarakah as financing product. The sampling technique used in this research is purposive sampling. The data collection uses questionnaire with 254 respondens of total sample who are SME who are enlisted in subdistricts in Yogyakarta. The data analysis applies descriptive and multiple linear regression analysis. The result of this research indicates: knowledge of products in sharia banking significantly affects the interest to use musyarakah as financing product, knowledge of Islamic work ethic in sharia banking, knowledge of profit sharing in sharia banking , knowledge of financing risk in sharia banking affect insignificantly toward the interest to choose musyarakah as financing product.